2015
DOI: 10.1002/ijop.12210
|View full text |Cite
|
Sign up to set email alerts
|

Word‐to‐picture recognition is a function of motor components mappings at the stage of retrieval

Abstract: Embodied approaches of cognition argue that retrieval involves the re-enactment of both sensory and motor components of the desired remembering. In this study, we investigated the effect of motor action performed to produce the response in a recognition task when this action is compatible with the affordance of the objects that have to be recognised. In our experiment, participants were first asked to learn a list of words referring to graspable objects, and then told to make recognition judgements on pictures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…Retrieval corresponds to the online reenactment of this previously experienced sensorimotor pattern. Growing evidence supports this assumption and indicates that encoding, consolidation and retrieval processes rely, at least partially, on sensory and motor features of experiences [6][7][8][9]. Furthermore, this view is consistent with numerous results in cognitive neurosciences in which similar sensory cortices were found to be activated during experience and recollection of a particular episode (for a review see [10]).…”
Section: Introductionsupporting
confidence: 81%
“…Retrieval corresponds to the online reenactment of this previously experienced sensorimotor pattern. Growing evidence supports this assumption and indicates that encoding, consolidation and retrieval processes rely, at least partially, on sensory and motor features of experiences [6][7][8][9]. Furthermore, this view is consistent with numerous results in cognitive neurosciences in which similar sensory cortices were found to be activated during experience and recollection of a particular episode (for a review see [10]).…”
Section: Introductionsupporting
confidence: 81%
“…This result is particularly interesting for our purpose because it confirms, on the one hand, that there is a memory of the consequences of our actions (see also Brouillet et al, 2015); and on the other, that the action one takes here and now to provide an answer has an effect on memory performance. Brouillet et al (2016) investigated whether the action performed at the recovery stage, could affect memory performance. The results showed an effect of motor compatibility.…”
mentioning
confidence: 99%
“…In Valid situations, expectations are satisfied, resulting in a sense of fluency. When expectations are not satisfied (i.e., Non-valid situations), it causes a sense of surprise and consequently, a fluency break (Brouillet et al, 2016; Whittlesea & Williams, 2001) that is observed by an increase in response time.…”
Section: Discussionmentioning
confidence: 99%